National Affiliation or Local Representation: When TFA Alumni Run for School Board - Rebecca Jacobsen; Tamara Wilder Linkow (Arizona State University, 2014)
Historically power to govern public schools has been delegated to local school boards. However, this arrangement of power has been shifting over the past half century and increasingly, local school boards are targeted as ineffective and antiquated. Teach For America (TFA), typically examined for its placement of teachers, also seeks to develop educational leaders and TFA now encourages and supports its alumni to run for local school boards. The involvement of a national organization, like TFA, with its own national education agenda in local school board elections may reflect the next step in the demise of local control. To investigate whether TFA's involvement in local elections represents the spreading of a national agenda at the expense of attention to local issues, this research examines campaign messages for both TFA alumni candidates and their opponents. Results indicate that TFA alumni candidates incorporate significantly more messages aligned with TFA than their opponents (35 vs. 11), but they also maintain a focus on local issues as measured by the number of local issue messages they also incorporate into their campaign literature. Rather than debating whether school boards have lost power, this research points to the need to better understand how local politics is changing and expanding as new voices enter the arena.